2020
DOI: 10.1111/dth.13286
|View full text |Cite
|
Sign up to set email alerts
|

Psychodermatology in Balkans: Knowledge, awareness, and practice patterns of dermatologists in Albania

Abstract: The aim of this study is to find out the practice patterns, awareness, and knowledge about psychodermatology in Albanian dermatologists. A survey questionnaire was sent to Albanian dermatologists by mail and distributed during a regional dermatology conference. The dermatologists were requested to provide information on demographic variables, level of training, referral patterns, degree of comfort in managing psychocutaneous disorders, awareness of community resources, and interest in continuing medical educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
4
20
1
Order By: Relevance
“…Southern India (42.2%), and in Balkans (79%). [13][14][15] Only 12% of dermatologists in our study attended more than one formal training of more than 6 h (4.8%) training and of more than 12 h (8%) training. It is worth noting that attending such training correlated significantly with age and years of experience (r = .26, P = .02).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Southern India (42.2%), and in Balkans (79%). [13][14][15] Only 12% of dermatologists in our study attended more than one formal training of more than 6 h (4.8%) training and of more than 12 h (8%) training. It is worth noting that attending such training correlated significantly with age and years of experience (r = .26, P = .02).…”
Section: Introductionmentioning
confidence: 84%
“…16 On the contrary only 31% of Balkan dermatologists reported frequent experience with PD disorders in their practices. 15 Other studies reported the prevalence of psychiatric comorbidity in dermatology clinics to be around 25% to 30%. 17 It is worth noting that the level of experience and years of practice in our study influenced the observation and identification of psychocutaneous conditions diagnosed by dermatologists (P = .03).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this context, it can be speculated that there may be a strong association between psychological conditions including stress, anxiety, depression, and hair loss along with acne. 26,27 It can also be considered that the wide use of face masks may also contribute to the increasing number of acne mechanica during the COVID-19 pandemic. 2,28 In this study, "genital warts" and "molluscum contagiosum" search terms were also investigated.…”
Section: Discussionmentioning
confidence: 99%